The effect of grain size distributions on acoutic wave velocities in porous rocks - Samsuri, Ariffin; Herianto, Herianto (2005)
This paper presents the result of the study to established correlation between grain size distribution and a acoustic wave velocities of the sandstone and limestone sample by using Ultrasonic Pulse Velocity Method (UPVM). This result also can be used in density and porosity determination by knowing the rock acoustic velocity data which normally can be estimated from acoustic log and seismic data.